Effects of Circuit Exercise Training Intervention on Health-Related Physical Fitness and Biomarkers for the Elderly People with Cardiovascular Diseases - Boudehri Mohamed El Amine, Belkadi Adel, Dahoune Oumri, Atallah Ahmed (G Y M N A S I U M Scientific Journal of Education, Sports, and Health, 2023)
This study aimed to investigate the effects of a 12-week circuit exercise intervention on the health-related physical fitness and biomarkers of elderly with cardiovascular diseases. Sixty-seven subjects participated in the study, included stretching, aerobic, and resistance training. Pre- and post-examination blood testing and fitness testing. Paired samples t-tests, and correlation analysis were used to analyse the data. Results showed that subjects were overweight and had medium risk levels of infection for cardiovascular diseases. Cardiovascular and strength performance improved, but sit-up performance was lower than the norm. Total cholesterol and systolic blood pressure improved, but systolic blood pressure remained at a pre-hypertension level. The intervention had a significant positive effect on health-related physical fitness and biomarkers with medium risk cluster of cardiovascular diseases, and there was a high correlation between the two. BMI had a positive correlation with biomarker index and cardiovascular fitness, while agility and flexibility had a negative correlation
Keywords: exercise training, intervention, cardiovascular risk, health-related physical fitness, biomarkers index